Enhanced Separation of Palladium from Nuclear Wastewater by the Sulfur-Rich Functionalized Covalent Organic Framework - Junli Wang; Chen Luo; Wentao Wang; Hui Wang; Yao Liu; Jianwei Li; Taihong Yan (Nanomaterials)
The separation of palladium from radioactive waste streams represents a critical aspect of the secure handling and disposal of such hazardous materials. Palladium, in addition to its radioactive nature, holds intrinsic value as a resource. Despite the urgency, prevailing adsorbents fall short in their ability to effectively separate palladium under highly acidic environments. To surmount this challenge, our research has pioneered the development of 1,3,5-tris(4-aminophenyl)benzene-2,5-Bis(methylthio)terephthalaldehyde COF (TAPB-BMTTPA-COF), a novel material distinguished by its remarkable stability and an abundance of sulfur-containing functional groups. Leveraging the pronounced affinity of the soft ligands’ nitrogen and sulfur within its molecular architecture, TAPB-BMTTPA-COF demonstrates an exceptional capability for the selective adsorption of palladium. Empirical evidence underscores the material’s swift adsorption kinetics, with equilibrium achieved in as little as ten minutes, and its broad tolerance to varying acidity levels ranging from 0.1 to 3 M HNO3. Furthermore, TAPB-BMTTPA-COF boasts an impressive adsorption capacity, peaking at 343.6 mg/g, coupled with high selectivity in 13 interfering ions’ environment and the ability to be regenerated, making it a sustainable solution. Comprehensive analyses, including Fourier Transform Infrared Spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS), alongside Density Functional Theory (DFT) calculations, have corroborated the pivotal role played by densely packed nitrogen and sulfur active sites within the framework. These sites exhibit a robust affinity for Pd(II), which is the cornerstone of the material’s outstanding adsorption efficacy. The outcomes of this research underscore the immense potential of COFs endowed with resilient linkers and precisely engineered functional groups. Such COFs can adeptly capture metal ions with high selectivity, even in the face of severe environmental conditions, thereby paving the way for the more effective and environmentally responsible management of radioactive waste.